Water extract of brewers' rice induces apoptosis in human colorectal cancer cells via activation of caspase-3 and caspase-8 and downregulates the Wnt/β-catenin downstream signaling pathway in brewers' rice-treated rats with azoxymethane-induced colon carcinogenesis - Tan, Bee Ling; Mohd Esa, Norhaizan; Ky, Huynh; Rahman, Heshu Sulaiman; Yeap, Swee Keong; Hamzah, Hazilawati; Karim, Roselina (BioMed Central, 2015)
Background: Brewers’ rice, is locally known as temukut, is a mixture of broken rice, rice bran, and rice germ. The current study is an extension of our previous work, which demonstrated that water extract of brewers’ rice (WBR) induced apoptosis in human colorectal cancer (HT-29) cells. We also identified that brewers’ rice was effective in reducing the tumor incidence and multiplicity in azoxymethane (AOM)-injected colon cancer rats. Our present study was designed to identify whether WBR confers an inhibitory effect via the regulation of upstream components in the Wnt signaling pathway in HT-29 cells. To further determine whether the in vitro mechanisms of action observed in the HT-29 cells inhibit the downstream signaling target of the Wnt/β-catenin pathway, we evaluated the mechanistic action of brewers’ rice in regulating the expressions and key protein markers during colon carcinogenesis in male Sprague–Dawley rats. Methods: The mRNA levels of several upstream-related genes in the Wnt signaling pathway in HT-29 cells treated with WBR were determined by quantitative real-time PCR analyses. Caspase-3 and −8 were evaluated using a colorimetric assay. Male Sprague–Dawley rats were administered two intraperitoneal injections of AOM in saline (15 mg/kg body weight) over a two-week period and received with 10, 20, and 40 % (w/w) brewers’ rice. The expressions and protein levels of cyclin D1 and c-myc were evaluated by immunohistochemical staining and western blotting, respectively. Results: The overall analyses revealed that the treatment of HT-29 cells with WBR inhibited Wnt signaling activity through upregulation of the casein kinase 1 (CK1) and adenomatous polyposis coli (APC) mRNA levels. We discovered that the treatment of HT-29 cells with WBR resulted in the induction of apoptosis by the significant activation of caspase-3 and −8 activities compared with the control (P < 0.05). In vivo analyses indicated that brewers’ rice diminished the β-catenin, cyclin D1, and c-myc protein levels. Conclusions: We provide evidence that brewers’ rice can induce apoptosis and inhibit the proliferation of HT-29 cells through regulation of caspase-dependent pathways and inhibit the Wnt/β-catenin downstream signaling pathway in vivo. We suggest that brewers’ rice may be a useful dietary agent for colorectal cancer.